Sob os caninos de Oswald / Under Oswald’s canine teeth - Feitosa, Susanna Busato (Revista de Letras, 2007)
Investigação estética acerca dos procedimentos de criação poética de Oswald de Andrade, tendo em vista a natureza antropofágica de sua poesia. Exploração dos aspectos inaugurados que sua fala projeta em termos culturais: manipulação original do material significante e articulação semântica de um novo viés lírico. An aesthetics investigation about the procedures in Oswald de Andrade’s poetic creation, in view of the nature anthropophagic nature of his poetry; an exploration of the inaugurating aspects that his speech projects in cultural terms: original manipulation of the significant material and semantic articulation of a new lyric perspective.